Audit commitee effectiveness among Malaysian listed companies - Abdullah, Shamsul Nahar; Ku Ismail, Ku Nor Izah (Universiti Utara Malaysia, 1999)
This study investigates further the previous paper by Shamsul Nahar and Al-Murisi (1997) by examining the interavtive effects of the variables in that paper and introducing other variables associated with corporate governance and political costs. The present study postulated that percentage of external directors on audit committee interacted with the presence of an accountant on audit committe and with the number of years and audit committe in existence, respectively, to influence audit committee effectiveness. The study also posited that the interaction of the presence of an accountant on audit committee and the number of years an audit committee in existence positively and significantly influenced audit committee effectiveness.